Signal transduction abnormalities in suicide: focus on phosphoinositide signaling system - Pandey, Ghanshyam N (CNS & neurological disorders drug targets, 2013)
Suicide is a major public health concern and each year about one million people die by suicide worldwide. Recent studies suggest that suicide may be associated with specific neurobiological abnormalities. Earlier studies of neurobiology of suicide focused on abnormalities of the serotonergic mechanism. These studies suggested that some serotonin receptor subtypes may be abnormal in the postmortem brain of suicide victims. Since these receptors are linked to signal transduction pathways, abnormalities of signaling mechanisms have been recently studied in the postmortem brain of suicide victims. Of particular interest is the 5-hydroxytryptamine2A receptor-linked phosphoinositide signaling system. Several studies have focused on the abnormalities on the component of this signaling system and these studies suggest the abnormalities of G proteins, the effectors phospholipase C and the second or the third messenger systems, such as protein kinase A. Further studies revealed abnormalities in the downstream transcription factors such as the cyclic AMP response element binding protein and some of the targeted genes of these transcription factors. The most important gene in this aspect which has been studied in the suicide is the brain-derived neurotrophic factor. Here we critically review the studies focusing on these components of the phosphoinositide signaling system in the postmortem brain of both adult and teenage suicide victims. These studies provide a better understanding of the signal transduction abnormalities in suicide focusing on the phosphoinositide signaling pathway. These studies may lead to new therapeutic agents targeting specific sites in this signaling cascade.